A Comparative Study Of Some Of The Epidemiologic Characteristics Of The Acceptors Of Vasectomy And Tubectomy In An Industrial Hospital - Samal R.K; Mukherjee P.K (Wolters Kluwer Medknow Publications, 1985)
The characteristics of 93 couples opting for vasectomy or tubectomy in an industrial hospital after an initial period of intensive health education activities are analysed and compared. The results indicate that the husbands in the vasectomy group were more educated, placed in better job categories and were earning more in comparison to those in the tubectomy group. The wives in the vasectomy group were also more educated. It was also observed that the couples opting for vasectomy belonged to older age groups but were having fewer number of living children in comparison to the couples opting for tubectomy. The hypothesis that couples from higher socio-economic strata might be tending to accept vasectomy as the method of choice in preference to tubectomy and its subsequent policy implications are discussed.